2018
DOI: 10.1016/j.jcrs.2017.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens power adjustment by a femtosecond laser

Abstract: Power adjustment of a commercially available hydrophobic acrylic blue light-filtering IOL by a femtosecond laser produced an accurate change in dioptric power while not significantly affecting the quality of the IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…104 A laboratory study has demonstrated the use of a femtosecond lens to change the refractive properties of an IOL ex vivo. 105 The FL device used in this study operated at an energy level below the threshold for ablation or cutting. It appears to induce chemical changes in the IOL substrate which affect its refractive index, without affecting the overall modulation transfer function of the IOL and is biocompatible in a rabbit model.…”
Section: Future Applications Of Flacs Under Current Investigationmentioning
confidence: 99%
“…104 A laboratory study has demonstrated the use of a femtosecond lens to change the refractive properties of an IOL ex vivo. 105 The FL device used in this study operated at an energy level below the threshold for ablation or cutting. It appears to induce chemical changes in the IOL substrate which affect its refractive index, without affecting the overall modulation transfer function of the IOL and is biocompatible in a rabbit model.…”
Section: Future Applications Of Flacs Under Current Investigationmentioning
confidence: 99%
“…Under slit lamp examination, the phase-wrapped structure created by the laser could be observed within the optic substance of all treated IOLs. The examination also showed the formation of gas bubbles between the posterior surface of the IOL and the posterior capsule, which disappeared within 5 h. Other observa- No aqueous flare, cells, iris hyperemia, or fibrin formations were observed at any of the post-laser slit lamp examinations, and the process did not create glistening's in the IOLs [34,35]. The consistency and precision of the power changes induced by the laser have been shown in vitro.…”
Section: Biocompatibility Of Intraocular Lens Power Adjustmentmentioning
confidence: 65%
“…FSL is also suggested to enable an adjustment of IOL power by increasing hydrophilicity of the target areas within the optic, creating a refractive index shaping lens within an existing IOL [110,111]. An in vitro study revealed that a negative refractive index change in the laser-treated optic areas resulting from the change in hydrophilicity might be the chemical basis for an alteration of the IOL power [112].…”
Section: Experimental Studies Regarding Potential Application Of the mentioning
confidence: 99%
“…An in vitro study revealed that a negative refractive index change in the laser-treated optic areas resulting from the change in hydrophilicity might be the chemical basis for an alteration of the IOL power [112]. An experimental study using a hydrophobic acrylic IOL revealed that power adjustment using FSL produced a reliable refractive change [111]. An animal study also showed that IOL power adjustment using FSL might be a precise, reliable, and biocompatible method for the correction of refractive error after cataract surgery [110].…”
Section: Experimental Studies Regarding Potential Application Of the mentioning
confidence: 99%